Patient experiences of as-needed budesonide-formoterol by Turbuhaler® for treatment of mild asthma; a qualitative study. (December 2020) - Foster, J.M.; Beasley, R.; Braithwaite, I.; Harrison, T.; Holliday, M.; Pavord, I.; Reddel, H.K.
Abstract: Background: Combination low-dose budesonide-formoterol, taken as-needed for symptom relief reduces exacerbation risk and is recommended for treatment of mild asthma. The NovelQ qualitative study explored patients' attitudes toward using this novel therapy. Methods: Adults with mild asthma using reliever-only treatment were randomised to as-needed budesonide-formoterol Turbuhaler® in a multinational, 52-week open-label randomised controlled trial (NovelSTART-ACTRN12615000999538). A subgroup were interviewed to explore their attitudes to use of as-needed budesonide-formoterol after receiving it for ≥10 months. Semi-structured interviews were conducted until saturation, audio-recorded, and thematically analysed. Results: Analysis of 35 participants (66% female; mean age 43.5 [range 18–74]; mean Asthma Control Questionnaire score 1.09 ± SD0.55) interviews identified 5 themes, each including both barriers and facilitators to therapy use. Themes were: 'Treatment effectiveness' i.e. how well symptoms were relieved and/or prevented; 'Lifestyle fit of the regimen' e.g. the extent to which the treatment regimen integrated into the patient's daily life; 'Attitudes toward medication use and safety' e.g. openness for new reliever treatments, beliefs about treatment necessity or side effects; 'Device attributes' e.g. perceived ease of use; and 'Doctor-patient relationship' e.g. impact of health professional support on new treatment acceptance. Conclusions: A wide range of factors seem to drive the opinions of mild asthma patients on as-needed budesonide-formoterol therapy. Many patients perceived both positive and negative treatment attributes, and their individual evaluation of these attributes determined their likelihood of using it after the study. Supportive patient-physician interactions appear key to addressing patient barriers. Recommendations for patient-centred discussions, developed from this research, are provided. Highlights: As-needed budesonide-formoterol therapy reduces exacerbation risk in mild asthma. Most patients consider the therapy safe and a good fit with their lifestyle. Often patients perceive both positive and negative therapy attributes. Unique patient factors promote/inhibit the use of as-needed budesonide-formoterol. Supportive patient-physician interactions are key to addressing patient barriers.